Analisis Pemilihan Supplier Pada Pengadaan Suku Cadang dengan Metode Analytic Hierarchy Process - Naufal, Mohammad Farid; Putra, Putu Aditya Riva; Kusuma, Selvia Ferdiana (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
PT. Bali Age is a company which engaged in freight forwarding service. Because of this, the company is using the trucks for carry out of their operational activities. Every truck always gets a routine maintenance at their garage, so they must provide the spare parts stock by themselves. The currently procurement of spare parts are still based on paper. By implementing the decision support in a new procurement system, it can provide a supplier recommendation for this company. This supplier recommendation which provides by system, are getting from the result of the comparation value from criteria priority calculation, using AHP method. The AHP method that implemented in this system, can also provide the final result of supplier recommendation comparison value with accurately.